Potential Fishing Ground For Tuna (Thunnus sp) Based On Mapping Of Sea Surface Temperature Distribution And Catches Data By Using Satellite Imagery Of Aquarius In Sumatra Waters - Emma Suri Yanti Siregar; Usman '; Arthur Brown (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The purpose of this study was to know the potential fishing ground of tuna(Thunnus sp) by mapping distribution of sea surface temperature satellite imageryof Aquarius and catched in waters of West Sumatra and then plotted estimated offishing ground in form of map. The analysis data was conducted in FishingGround Laboratory Faculty of Fisheries and Marine Sciences University of Riau,Pekanbaru. This study using Aquarius satelite imagery data level 3, with a 4 kmspatial resolution. In this study sea surface temperature ranging from 27,040C–30,170C. Tuna was catched dominantly temperature in west season is in range27,090C–29,280C, transition season I 27,040C–30,170C, east season 28,690C–29,820C and transition season II 27,320C–29,540C. The catched with CPUEhighest value 7.5963 kg/day in August. The catches of all tuna is category viablecatch. The potential fishing ground were found ground of Siberut and Siporaisland waters.Keywords : Sea Surface Temperature, Satelite Imagery, Aquarius, T. Albacares,T.obesus.